Conservation of forage germplasm with an emphasis on application of tissue culture techniques in a genebank - Hanson, Jean; Mtambo, P.J.; Ruredzo, T.J. (1992)
Conservation of germplasm has traditionally relied to a large extent on storage of seeds in genebanks. However, some forage species may take a long time to research maturity and produce seeds or, in the case of grasses, have inadequate production of seeds for collection, multiplication, dissemination and utilization. In vitro culture techniques have a potential use for those tropical forage legumes and grasses which cannot be conveniently handled by conventional methods as an alternative method to field genebanks for genetic resources management. This paper discusses the conservation of forage germplasm with an emphasis on application of tissue culture techniques in a genebank. Topics of discussion include seed storage; conservation in field genebanks, use of in vitro culture for germplasm management, in vitro culture research at ILCA, distribution of germplasm; duplication; and seed multiplication and characterisation. It also lists forage germplasm in the ILCA genebank and the major genera in the ILCA genebank.